The effect of masks on the recognition of facial expressions: A true-to-life study on the perception of basic emotions - Leitner, Michael Christian; Meurer, Verena; Hutzler, Florian; Schuster, Sarah; Hawelka, Stefan (Frontiers in Psychology, 2022)
Mouth-to-nose face masks became ubiquitous due to the COVID-19 pandemic. This ignited studies on the perception of emotions in masked faces. Most of these studies presented still images of an emotional face with a face mask digitally superimposed upon the nose-mouth region. A common finding of these studies is that smiles become less perceivable. The present study investigated the recognition of basic emotions in agitated faces (i.e., we video-taped facial expressions of emotions). We replicated much of the evidence gathered from presenting still images with digitally superimposed masks. We also unearthed fundamental differences in comparison to existing studies with regard to the perception of smile which is less impeded than previous studies implied.